Persistence of The Tarekat Naqsabandiyah in Local Politics of Indonesia Post New Order - Tito Handoko; Abdul Munir Mulkan; Mega Hidayati; Muhammad Azhar (UIN Sunan Gunung Djati Bandung, 2021)
In the Indonesian context, tarekat is seen as a social movement with a broad impact. Its existence and activity need to be paid attention to by the State, society, and other political infrastructure. Many experts have carried out the discourse on tarekat with various points of view. This study focuses on the socio-political sphere of tarekat and its movements in local Indonesian politics after the Soeharto Era using a qualitative approach with interpretive data analysis involving the informants who understand the tarekat activity in Rokan Hulu in depth. The emergence of spiritual organs with various ideological variants, visions, and missions indicates the strengthening of civil supremacy in Indonesia. As part of a religious civil society organization, the Naqsyabandiyah order can grow and exert a strong influence on the dynamics of Indonesian local democracy, especially in Rokan Hulu - Riau. The existence of this movement strengthens Bruinessen's argument about the tarekat as a